The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1089/ten.tea.2016.0274
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned Medium from Periodontal Ligament Stem Cells Enhances Periodontal Regeneration

Abstract: Periodontal disease is one of the most common infectious diseases in adults and is characterized by the destruction of tooth-supporting tissues. Mesenchymal stem cells (MSCs) comprise the mesoderm-originating stem cell population, which has been studied and used for cell therapy. However, because of the lower rate of cell survival after MSC transplantation in various disease models, paracrine functions of MSCs have been receiving increased attention as a regenerative mechanism. The aim of this study was to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 136 publications
(146 citation statements)
references
References 43 publications
3
137
0
Order By: Relevance
“…Stem/Progenitor Cell-Derived Secretome/Conditioned Medium The periodontal ligament is considered a potent source of stem/progenitor cells for tissue regeneration that can differentiate into several types of cells [178][179][180]. They are the most favorable stem/progenitor cell population utilized in periodontal regeneration [181], due to their high expression of scleraxis, a protein responsible for the formation of the cementum-periodontal ligament complex [37]. Human periodontal ligament MSCs are similar to bone marrow MSCs, with high proliferative rate, immunomodulatory functions, and an in vitro differentiation ability into osteogenic, adipogenic, chondrogenic, and neurogenic cell lineages [182][183][184].…”
Section: Periodontal Ligaments Mesenchymalmentioning
confidence: 99%
“…Stem/Progenitor Cell-Derived Secretome/Conditioned Medium The periodontal ligament is considered a potent source of stem/progenitor cells for tissue regeneration that can differentiate into several types of cells [178][179][180]. They are the most favorable stem/progenitor cell population utilized in periodontal regeneration [181], due to their high expression of scleraxis, a protein responsible for the formation of the cementum-periodontal ligament complex [37]. Human periodontal ligament MSCs are similar to bone marrow MSCs, with high proliferative rate, immunomodulatory functions, and an in vitro differentiation ability into osteogenic, adipogenic, chondrogenic, and neurogenic cell lineages [182][183][184].…”
Section: Periodontal Ligaments Mesenchymalmentioning
confidence: 99%
“…We have previously reported that decreased levels of tumor necrosis factor α (TNFα) were correlated with the regeneration of periodontal tissues; this suggested positive relationships between the inhibition of inflammation and periodontal regeneration. 35 These results, together with the enhanced gene expression in PDLSC spheroid, inspired us to examine the regenerative function of PDLSC spheroids in vivo. However, we did not find the regeneration of periodontal tissues by transplanting of PDLSC spheroids into periodontal defects in rats, although the sample size was small.…”
Section: Discussionmentioning
confidence: 99%
“…Male nude rats were used in this study (F344/N‐Jcl‐rnu/rnu; 7‐10 weeks of age; n = 6). Surgical procedures were performed as described in previous studies . Briefly, an incision of 1‐1.5 cm was made at the bottom of the mandible, and the buccal plate was exposed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations